Determinants of Farmers\' Health Behaviors on Poisoning with Pesticides in Golestan Province: Based on the Health Belief Model - Ali Zafarzadeh; Abotaleb Bay; Seyed Kamal Mirkarimi; Ahmad Heidari (Golestan University of Medical Sciences, 2019)
Background: Pesticides are chemical compounds which are used to fight against and to control plant and animal pests as vectors of diseases. In view of being exposed to pesticides, farmers are at high risk of occupational diseases. In this regard, the predictability of Health Belief Model (HBM) has been confirmed for the studies in promoting health behaviors. The aim of the study was to investigate the determinants of health behaviors of farmers on poisoning with pesticides in Golestan province based on HBM. Methods: A cross-sectional study was conducted on 294 farmers covered under Health centers in Azadshahr, Golestan province in 2015. A multi-stage sampling method was used. Data was collected through HBM questionnaire and analyzed using Pearson and Spearman rank correlation coefficient, one-way ANOVA, and linear regression model in SPSS-16. The P-value was considered significant as <0.05. Results: The mean age of participants was 46.12±11.45 years (ranged from 17 to 75). The majority of participants was under diploma (60.1%) and used television educational programs (76.9%) as main source of information and chemical dealers (68.4%) as main cues to action. There was a significant correlation between educational status and the amount of pesticide (p=0.024). In final, perceived barriers was the variable for predicting the healthy behavior of farmers (β= 0.208, p=0.004). Conclusions: The results presented in this study recommend that since the majority of farmers were awarded high school diploma, designing and developing effective interventions in order to promote knowledge and perceived self-efficacy should be considered.